Comparative Evaluation of Selected Grass Species for Agronomic Performance, Forage Yield, and Chemical Composition in the Highlands of Ethiopia - Aysheshim Bantihun; Bimrew Asmare; Yeshambel Mekuriaw (Advances in Agriculture)
The study was conducted to determine the effect of different grass species (Brachiaria mutica, Desho, and Napier) and harvesting stages on agronomic performance, forage dry matter yield, and chemical composition. The grass species used were Desho (Pennisetum pedicellatum), Brachiaria (Brachiaria mutica), and Napier (Pennisetum purpureum), and the harvesting stages considered were 60, 90, and 120 days after establishment of grasses, respectively. The data collected included the following: percent plant survival (PS), plant height (PH), number of tillers per plant (NTPP), number of leaves per plant (NLPP), leaf length per plant (LLPP), leaf width per plant (LWPP), number of nodes per plant (NNPP), leaf-to-stem ratio (LSR), dry matter yield (DMY), and chemical composition of the grass species. Samples of grass species were harvested at different ages after establishment, weighed, and dried, and then, ground subsamples were taken for determination of dry matter (DM), ash, organic matter (OM), crude protein (CP), crude protein yield (CPY), acid detergent fiber (ADF), neutral detergent fiber (NDF), and acid detergent lignin (ADL). Results showed that morphological characteristics, forage dry matter yield, and chemical composition of the forage grasses were significantly affected by interactions of species (P<0.001) and harvesting dates. The highest mean PH (115.2 cm), DMY (11.8 t/ha), and %CP (11.6) were recorded from Brachiaria mutica grass which was followed by Napier grass with mean PH of 87.25 cm and mean DMY of 9.8 t/ha. The %CP content of Desho and Napier grasses declined by 24%, while %CP content of Brachiaria grass declined by 26% with increased harvesting stages. Therefore, among tested grass species, Brachiaria mutica grass was recommended followed by Napier and Desho grass for on-farm evaluation and demonstration in the study area at all harvesting ages. Farmers engaged in forage grass production could seriously consider the harvesting stage as the grasses responded differently to the chemical composition.